Corruption and Marriage Agreements Legal Analysis of Property Ownership - Rafiqi; Montayana Meher; Fitri Yanni Dewi Siregar (Faculty of Law, Universitas Pekalongan, 2025)
Major corruption cases such as the Bank Century, e-KTP, Tambang and BLBI scandals are examples of how corruption can involve high-ranking officials and cost the state trillions of rupiah long marriage Agreement made by a husband and wife before or during marriage which regulates the Purpose of the Marriage Agreement Regulates separation or division of assets acquired during and before marriage. Prevent disputes related to assets in the event of divorce, corruption or death of one of the partners. The research method used is Normative Juridical. Separation of Assets Based on the Marriage Agreement. Assets are based on Article 29 of Law Number 1 of 1974 concerning Marriage and Articles 119-131 of the Civil Code. Relationship with Assets Assets obtained from corruption can be confiscated by the state if they are proven to be related to a criminal act. Legal Responsibility If one spouse is involved in a corruption case, the assets obtained from the corruption act can be separated from the assets of the other spouse who is not involved. Refrences Ahyani, S. (2018). Implikasi Putusan Mahkamah Konstitusi Nomor 69/Puu/Xiii/2015 Terhadap Pasal 29 Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan. Jurnal Wawasan Yuridika, 2(1), 84-98. Akbar, M. (2023). Izin Atasan Dalam Perceraian Pegawai Negeri Sipil (Studi Kasus Bkpsdmd Kota Parepare) (Doctoral Dissertation, Iain Parepare). Andhika, N. A. (2022). Akibat Hukum Perjanjian Perkawinan Terhadap Harta Bersama Pasca Perceraian (Studi Putusan Nomor 2454/Pdt. G/2018/Pa. Smg) (Doctoral Dissertation, Universitas Islam Sultan Agung). Andhika, N. A. (2022). Akibat Hukum Perjanjian Perkawinan Terhadap Harta Bersama Pasca Perceraian (Studi Putusan Nomor 2454/Pdt. G/2018/Pa. Smg) (Doctoral Dissertation, Universitas Islam Sultan Agung). Antara, D. P. (2024). Jurus Mengelola Badan Dharma Dana Punia. Nilacakra. Awaludin, A., & Waluyo, B. (2023). Perlindungan Hukum Atas Harta Perkawinan Melalui Aktaperjanjian Kawin. Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 25(1), 22-32. Edlynafitri, R. S. (2015). Pemisahan Harta Melalui Perjanjian Kawin Dan Akibat Hukumnya Terhadap Pihak Ketiga. Lex Privatum, 3(1). Hasibuan, N. H. Tata Kelola Aparatur Sipil Negara Dalam Mewujudkan Reformasi Birokrasi (Studi Uu No. 20/2023 Tentang Aparatur Sipil Negara) (Bachelor's Thesis, Fakultas Syariah Dan Hukum Uin Syarif Hidayatullah Jakarta). Istiyanto, R., Idham, I., & Fadlan, F. (2021). Perlindungan Hukum Rekruitmen Pekerja Alih Daya Guna Meneguhkan Kepastian Hukum. Jatiswara, 36(3), 311-324. Juhaeni, J. (2021). Penyalahgunaan Wewenang Oleh Pejabat Publik Dalam Perspektif Sosiologi Hukum. Jurnal Konstituen, 3(1). Kumorotomo, W. (2007, June). Citizen Charter (Kontrak Pelayanan): Pola Kemitraan Strategis Untuk Mewujudkan Good Governance Dalam Pelayanan Publik. In Paper In The Seminar Of Persadi, Hotel Ibis, Pekanbaru (Vol. 16). Manafe, J. D., Nino, I. J., & Setyorini, T. (2018). Model Pelaporan Keuangan Dengan Menggunakan Sistem Akuntansi Sederhana Bagi Ritel Manajemen Umkm Di Kota Kupang. Bisman-Jurnal Bisnis & Manajemen, 3(01), 36-47. Melati, D. P. (2022). Refungsionalisasi Hukum Pidana Adat Lampung Dalam Sistem Penegakan Hukum Pidana Berbasis Kearifan Lokal Ndraha, S., Daya, T. T., Silaban, R., & Nurita, C. (2025). Perlindungan Hukum Terhadap Harta Bawaan Dengan Membuat Akta Perjanjian Perkawinan. Diktum, 3(3), 98-104. Nurnazli, N. (2019). Analisis Putusan Mahkamah Agung Tentang Pembagian Harta Bersama Dan Implikasinya Terhadap Pembaruan Hukum Keluarga Di Indonesia (Doctoral Dissertation, Uin Raden Intan Lampung). Pranoto, A., Darmo, A. B., & Hidayat, I. (2019). Kajian Yuridis Mengenai Perampasan Aset Korupsi Dalam Upaya Pemberantasan Tindak Pidana Korupsi Menurut Hukum Pidana Indonesia. Legalitas: Jurnal Hukum, 10(1), 91-121. Pratama, Y. (2021). Keputusan Hukum Perjanjian Perkawinan Yang Tidak Didaftarkan Pada Kantor Pencatatan Perkawinan. Jurnal Ilmiah Mahasiswa Hukum [Jimhum], 1(4). Putra, G. G. G. M. (2017). Penyalahgunaan Hak Terhadap Objek Sita Marital Berupa Tanah Dan Bangunan Dihubungkan Dengan Kitab Undang-Undang Hukum Pidana (Doctoral Dissertation, Fakultas Hukum Universitas Pasundan). Rahadini, E. (2021). Disfungsi Peran Notaris Dalam Perjanjian Kredit Yang Menyebabkan Kerugian Negara Di Wilayah Kabupaten Purbalingga:(Studi Kasus Putusan Pengadilan Negeri Tindak Pidana Korupsi Semarang Nomor: 72/Pidsus-Tpk/2019/Pn Smg Dan Nomor 73/Pidsus-Tpk/2019/Pn Smg.) (Master's Thesis, Universitas Islam Sultan Agung (Indonesia)). Sukowati, P. (2011). Perubahan Sosial & Kebijakan Pembangunan Berwawasan Lingkungan. Waluyo, B. (2022). Pemberantasan Tindak Pidana Korupsi: Strategi Dan Optimalisasi. Sinar Grafika. Wardojo, M. F. (2018). Kedudukan Komisi Pemberantasan Korupsi Sebagai Lembaga Negara. Legal Standing: Jurnal Ilmu Hukum, 2(1), 73-83.